INFECTION AND TRANSMISSION PATTERN OF SCHISTOSOMIASIS IN IRRIGATION SCHEMES AROUND KHARTOUM STATE, SUDAN - Elamin Osman, Elbadri; Mohamed Hilali, Abdelmoneim Hassan; Sayed Koko, Waleed (Gezira Journal of Health Sciences, 2005)
Schistosomiasis (prevalence, intensity and incidence) and patterns of transmission were studied in two villages lying within the irrigated area around Khartoum State i.e. Kiryab in Seilate Scheme, East Nile Province and Baraka in Gamooeya Scheme, Omdurman Province (1996 - 1998). Both types of infection were recorded in Kiryab village while only the intestinal form, S. mansoni , was found in Baraka village.Prevalence and intensity of S. haematobium infection among people living in Kiryab village were 33.5% and 122.5 eggs/10 ml and those of  S. mansoni were 17.6% and 199.6 eggs/g respectively. Prevalence and intensity of S. mansoni infection were 40.8% and 136.1 eggs/g in Baraka. Incidence rates among schoolchildren were 5.2% and 6.7% for S. haematobium and  S. mansoni  in Kiryab respectively and 10.9% for S. mansoni  in Baraka. The overall prevalence and intensity of both types of schistosomiasis varied between the two villages of the study and in each village these indices of infection varied significantly according to age, reaching a peak in the age group 10 –19 years.Seven different species were found in snail sampling sites in the irrigation canals around the study villages. These snail species were the pulmonates: Biomphalaria pfiefferi, Bulinus truncatus, Lymnea natalensis, Physa acuta and Bulinus forskalii and the prosobranchs: Cleopatra builimoides and Melanoides tuberculata . Pulmonates in general and the schistosome intermediate hosts (i.e. B. pfiefferi and B. truncatus ) in particular were observed to vary in distribution and density according to season reaching a peak in the hot season from March to June. Transmission of infection was found to be focal and highly seasonal taking place during summer period from March to June.